FORMATION OF FASTNESS IN THE CREATED RIDGES OF THE GROIN (British Journal of Global Ecology and Sustainable Development, 2024)
The article analyzes the growing season of the ridges created by the authors, mainly the indicators “germination-50% flowering” and“germination-50% ripening”. As a result of studies, t-340 and T-160 ridges have been isolated in frequency, and they have been recommended for future use in genetic-selective research.